Firm Value in The SRI-KEHATI Index : Audit Committees, Independent Commissioners, Corporate Social Responsibility, Investment Opportunity Set, and Firm Size - Aulia Wilianti; Esi Fitriani Komara (Indonesian Scientific Publication, 2026)
Among the companies included in the SRI-KEHATI index, this study looks at the impact of audit committees, independent boards of commissioners, firm size, corporate social responsibility, investment opportunity sets, and firm value from 2020 to 2024. In this study, ten firms that were part of the SRI-KEHATI index from 2020 to 2024 are examined. Secondary data is sourced from company and Indonesia Stock Exchange publications, including annual reports, sustainability reports, and financial reports. We employed panel-data regression with a Random-Effects Model and conducted Chow and Hausman tests to determine which model was the most reliable and appropriate for drawing conclusions. Using a random-effects panel regression, the number of audit committee members is negatively associated with Tobin’s Q. The proportions of independent commissioners, CSR disclosure, and IOS are not statistically significant. In contrast, firm size is positively associated with Tobin’s Q. These findings suggest that firm size demonstrates a stronger association with firm value than the CSR, IOS and corporate governance proxies used in this study. This study provides new evidence that, within sustainability-screened firms in the SRI-KEHATI Index, corporate governance and CSR mechanisms function more as baseline requirements than as value-enhancing signals, making firm size the dominant determinant of market-based firm value. The findings of this study should be useful for management, investors, and future research on the topic of sustainability-based corporate value.